Comparative Analysis of Time and Cost Efficiency in Project Acceleration Strategies: A Case Study of the Construction of a Police Service Building - Afrida, Widia Dini; Renjani, Muhammad Sodri; Rahmawati, Devit; Radinal, Radinal (Civiliza Publishing, Indonesia., 2025)
Optimal time and cost management are fundamental factors in ensuring the success of construction projects. One effective approach to address the risk of delays and cost overruns is the Time Cost Trade-Off (TCTO) method, which allows for project duration compression through resource adjustment and cost control. This study aims to analyze and compare two acceleration scenarios for the construction of the Police Service Building in Bungo Regency: additional working hours (overtime) and additional labor. This study uses a descriptive quantitative approach through a case study. The Critical Path Method (CPM) is applied to identify the critical path as the basis for implementing the TCTO strategy. The results of this study indicate that both scenarios can accelerate the project duration from 214 days to 130 days, with a time efficiency of 39.25%. The overtime scenario provides a cost efficiency of 0.38%, while additional labor results in an efficiency of 0.16%. Although overtime is more economical in nominal terms, the additional labor strategy is considered more stable and feasible to implement in public projects with sufficient work space. The results of this study contribute to strategic decision-making in data-driven construction project management.